The influence of media exposure, political engagement, peer influence, and national identity on ideological beliefs among Malaysian public university students - Riccardo, Canova; Ma’rof, Aini Azeqa; Adnan, Zatul Himmah (Human Resource Management Academic Research Society, 2024)
Ideological beliefs play a critical role in shaping political, social, and cultural dynamics, particularly among young adults who represent the future of civic and political engagement. In Malaysia, where a multicultural society interacts with a rapidly evolving political landscape, understanding the factors influencing ideological beliefs is crucial for fostering informed and engaged citizens. This study investigates the influence of media exposure, political engagement, peer influence, and national identity on ideological beliefs among Malaysian public university students. Using a sample of 407 participants, this research employed quantitative methods, including Pearson correlation and multiple regression analyses, to examine these relationships. The results revealed that political engagement was the strongest predictor of ideological beliefs, followed by media exposure, peer influence, and national identity. These findings underscore the importance of active political participation, media consumption, and social interactions in shaping students' ideological development, while national identity also played a significant role, though with a slightly weaker influence. The study’s implications suggest that fostering political engagement, media literacy, and peer- driven discussions in educational settings can effectively contribute to the formation of informed ideological beliefs among young adults. The insights derived from this research offer valuable guidance for policymakers, educators, and institutions aiming to promote civic engagement and political awareness in Malaysia.